Covid‐19 vaccination during the third trimester of pregnancy: rate of vaccination and maternal and neonatal outcomes, a multicentre retrospective cohort study. (6th October 2021) - Rottenstreich, M; Sela, HY; Rotem, R; Kadish, E; Wiener‐Well, Y; Grisaru‐Granovsky, S
Abstract : Objective: To evaluate the impact of Covid‐19 vaccination (Pfizer–BioNTech BNT162b2) during the third trimester of pregnancy on maternal and neonatal outcomes. Design: A multicentre, retrospective computerised database. Population: Women who gave birth at >24 weeks of gestation in Israel, between January and April 2021, with full records of Covid‐19 disease and vaccination status. Methods: Women who received two doses of the vaccine were compared with unvaccinated women. Women who were recorded as having disease or a positive Covid‐19 polymerase chain reaction (PCR) swab during pregnancy or delivery were excluded from both study groups. Univariate analysis was followed by multivariate logistic regression. Main outcome measures: Composite adverse maternal outcomes. Secondary outcomes were vaccination rate and composite adverse neonatal outcomes. Results: The overall uptake of one or both vaccines was 40.2%; 712 women who received two doses of the Covid‐19 vaccine were compared with 1063 unvaccinated women. Maternal composite outcomes were comparable between the groups; however, women who received the vaccine had higher rates of elective caesarean deliveries (CDs) and lower rates of vacuum deliveries. An adjusted multivariable logistic regression analysis demonstrated that Covid‐19 vaccination was not associated with maternal composite adverse outcome (aOR 0.8, 95% CI 0.61–1.03); a significant reduction in the risk for neonatal composite adverse outcomes was observed (aOR 0.5, 95% CI 0.36–0.74). Conclusions: In a motivated population covered by a National Health Insurance Plan, we found a 40.2% rate of vaccination for the Covid‐19 vaccine during the third trimester of pregnancy, which was not associated with adverse maternal outcomes and, moreover, decreased the risk for neonatal adverse outcomes. Tweetable abstract: Covid‐19 vaccine during pregnancy is safe for both mother and fetus. Tweetable abstract: Covid‐19 vaccine during pregnancy is safe for both mother and fetus.